2015
DOI: 10.1007/s10971-015-3828-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of Gossypium hirsutum seeds extract nanoencapsulated in silica microparticles

Abstract: Nanoencapsulation of pharmaceutically active natural compounds into porous systems through sol-gel method leads to new drug delivery materials with sustained release behaviour of the entrapped pharmaceuticals. Properties of inorganic sol-gel-derived silica microparticles loaded with cotton (Gossypium hirsutum) seeds extract are reported. Xerogels obtained by heat or freeze drying were investigated by X-ray diffraction, dynamic light scattering, differential thermal analysis (DTA)/thermogravimetric analysis (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In response to the constant level of phosphatidyl choline, with the increase of extract, the loading level and encapsulation efficiency were lowered, and at the centrifugation step, they expose low stability. The extract of Gossypium hirsutum was encased by nanoliposomes, and it was reported that, by increasing the extract in the formulation, the stability of the system was lowered . Besides, Ostwald ripening is a significant factor responsible for the instability of the emulsion systems and nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…In response to the constant level of phosphatidyl choline, with the increase of extract, the loading level and encapsulation efficiency were lowered, and at the centrifugation step, they expose low stability. The extract of Gossypium hirsutum was encased by nanoliposomes, and it was reported that, by increasing the extract in the formulation, the stability of the system was lowered . Besides, Ostwald ripening is a significant factor responsible for the instability of the emulsion systems and nanostructures.…”
Section: Resultsmentioning
confidence: 99%